Endocannabinoid-Hydrolysing Enzymes in the Post-Mortem Cerebellum of Humans Affected by Hereditary Autosomal Dominant Ataxias - Rodríguez-Cueto, Carmen; Benito, Cristina; Romero, Julián; Hernández-Gálvez, Mariluz; Gómez-Ruiz, María; Fernández-Ruiz, Javier (Pathobiology (Basel), 2014)
Objectives: Spinocerebellar ataxias (SCAs) are characterized by a loss of balance and motor coordination due to degeneration of the cerebellum and its afferent and efferent connections. We recently found important changes in cannabinoid CB 1 and CB 2 receptors in the post-mortem cerebellum of patients affected by different SCAs. Methods: We wanted to further explore this issue by analysing the two major endocannabinoid-hydrolysing enzymes, fatty acid amide hydrolase (FAAH) and monoacyl glycerol lipase (MAGL), in the post-mortem cerebellum of SCA patients and control subjects. Results: Immunoreactivity for the FAAH and MAGL enzymes was found in the granular layer, in Purkinje cells, in neurons of the dentate nucleus and in areas of white matter in the cerebellum of patients at levels frequently notably higher than those in control subjects. Using double-labelling procedures, we found co-localization of FAAH and MAGL with calbindin, supporting the presence of these enzymes in Purkinje neurons. Conclusions: Degradative endocannabinoid enzymes are significantly increased in the cerebellum of SCA patients, which would presumably lead to reduced endocannabinoid levels. The identification of these enzymes in Purkinje neurons suggests a relationship with the pathogenesis of SCAs and suggests that the endocannabinoid system could provide potential therapeutic targets for the treatment of disease progression in SCAs.